Inserção laboral de travestis e transexuais na cidade de São Paulo: o Programa TransCidadania - Santana, Chinaira Raiazac Faria (2017)
The present study composes the "Policies of the Body" research line of the NIP - INANNA Research Center of the Social Psychology Program of the Pontifical Catholic University of São Paulo (PUCSP). Its general objective has as its starting point a discussion about the labor scene of transvestites and transsexuals, specifically to problematize the 'Transpassion Program' of the city of São Paulo, implemented by its municipality in 2015, in the management of Fernando Haddad (2013-2016). The political project of the Transpassion Program that breaks with limited optics to the training in the labor axis, when being proposed to a humanistic formation thought of education, emancipation and access to citizenship to combat the social vulnerability to which these people are exposed. It is an international showcase that has been presented here since its pilot project: the Operation LGBT Work Program - POTLGBT. This research is qualitative based. In order to subsidize their performance, we sought to present a bibliographical survey and analysis relevant to citizenship, labor market, social constitution of transvestites and transsexuals, their insertion in the labor market, and the obstacles and setbacks expressed by religious representatives in the sectors of Brazilian party policy, besides presenting the structure of the TransCitizenhip Program. The field of research presents six of research that are divided in two modalities of interview: In the first modality three (3) people interviewed correspond to the operational and management personnel of the Program, being: (1) Political Project Memory – POTLGBT, (1) The Coordination Assistance of the TransCitizenship Program and (1) Pedagogy of the TransCitizenship Program. The second modality presents an analysis of the life itineraries of three (3) users of the TransCitizenhip Program. It seeks to understand the impact of this Program on the lives of these users. Users' access was provided through lectures and voluntary chats coordinated by the researcher directly in the TransCitizenship Program in the year 2016 as part of the research process. In this research we present some of these artistic productions of expression on labor trajectories that were conceived in these meetings by transvestite women, transsexuals and trans men and users of the TransCitizenship Program. The interest in the theme is justified by the importance of its social demands besides aligning itself with the social commitment of a Psychology that aims to act in the social transformation, along with the social movements and articulations that fight for the promotion and guarantee of the social rights. To problematize the configurations of the exercise of citizenship of this population in the employment sector based on education and emancipation confers to the research a relevance correlated to the promotion of citizenship and human rights of the population of transvestites and transsexuals